Reliability and construct validity of the test of gross motor development-2 in Portuguese children. Issue 3 (4th May 2018) - Lopes, Vítor P.; Saraiva, Linda; Rodrigues, Luis P.
Abstract : The use of several different assessment motor tools make difficult to make comparisons of childhood motor competence across countries. Although the Test Gross Motor Development 2 (TGMD-2) is one of the most used instruments for assessing motor competence, its validation for Portuguese population is needed. The aim of the article is to examine the psychometric proprieties of the TGMD-2, using a Portuguese sample. Totally 330 children aged 5–10 years were assessed with TGMD-2. Cronbach's alpha assessed internal consistency. Test–retest reliability was estimated with the Bland–Altman method. Construct validity was assessed by a confirmatory factor analysis (CFA). The hypothesised model used 12 items and 2 factors: object control and locomotor skills. The test–retest reliability analysis was good, with an agreement ratio of .96 (.09) for 12 skills. Cronbach's alpha values showed acceptable internal consistency (.69 for 12 items, .46 for locomotor skills, and .64 for object control skills). The results of the CFA [CFI = .956, NFI = .868, NNFI = .937, SRMR = .048, and RMSEA = .036 (90% CI: .010–.054)] support the two-factor structure of the original version. Portuguese TGMD-2 version is a reliable and valid tool to assess the gross motor skills of Portuguese children aged 5–10 years.